Influence of grainless ration on nutrient intake and blood constituents in ruminant - SINGH, A S; SINGH, P; PATHAK, N N (The Indian Journal of Animal Sciences, 2014)
Study was undertaken to investigate the influence of grainless ration in relation to blood constituents of ruminant; a feeding experiment was conducted on 10 adult cattle (about 7 years of age), randomly divided into 2 groups of 5 animals each. Groups 1 and 2 animals were fed WB and DORB based grainless rations, respectively, to fulfil the maintenance requirement of CP along with wheat straw for 4 months. The nutrient intake and blood profile studies were carried out. The mean values of EE intake and blood biochemical constituents like glucose, total protein, inorganic phosphorus and cholesterol were 101.94± 4.07 and 63.27± 1.66 g; 48.24± 0.46 and 56.99± 0.48 mg/100 ml; 6.52± 0.08 and 7.20± 0.10 g/100 ml; 4.51± 0.06 and 5.81± 0.08 mg/100 ml and 1 19.08±4.21 and 94.04±2.36 mg/100 ml for groups 1 and 2, respectively, which shows significant differences (P